PERAN DAN TANTANGAN BANK SYARIAH INDONESIA DALAM MENINGKATKAN INKLUSI KEUNGAN MELALUI PRODUK MIKRO SYARIAH - Anisak; Saiful Bakhri (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2024)
Financial inclusion is an important aspect of sustainable economic development. Bank Syariah Indonesia (BSI), as the largest sharia bank in Indonesia, has a strategic role in expanding access to public financial services, especially through micro sharia products. This article aims to explore BSI's role in increasing financial inclusion and the challenges it faces in implementing sharia micro products. Through empirical data analysis studies, this article identifies various challenges such as low financial literacy, technological limitations, and high operational costs. This research uses a qualitative descriptive method. The research results show that BSI has great potential in expanding financial access for lower society, but requires more effective strategies to overcome various obstacles.